About Distributed Internal and Surface Strain Measurements within Prestressed Concrete Truck Scale Platforms. Issue 5 (February 2019) - Sienko, Rafal; Bednarski, Lukasz; Howiacki, Tomasz
Abstract: Distributed optical fibre measurement technology provides new possibilities in structural technical condition assessment in comparison with traditional spot measurements. It is not only possible to analyse strains continuously over structural member length with spatial resolution starting from as fine as 5 mm, but also the cracks and displacements state within reinforced concrete structures. The article presents pilot studies regarding prestressed concrete track scale platforms with a length of 8 to 16 m. Optical fibres were glued within composite rods attached to the stirrups inside the cross section of the slab on the height of lower and upper prestressing tendons, as well as they were glued to the concrete surface after bonding. That allows for comprehensive analysis of concrete strains state including all local nonlinearities (cracks) starting from hydration process (thermal-shrinkage strains), through prestressing tendons activation (strains regarding the transfer of compression forces from the tendond to the concrete) and finally during laboratory tests, when slabs were mechanically loaded until destruction. The ways of installation and exemplary results from selected phases of the research were presented as well as data interpretation was described and discussed.